Improving Activity and Learning Outcomes Through Group Work via WA Group - Leuwol, Ferdinand Salomo; Nurhayati, Nurhayati; Arifin, Zainul; Sedubun, Stenlly; Waruwu, Dermawan (Al-Hijr: Journal of Adulearn World, 2024)
The covid-19 pandemic has a huge impact on human activities, including the education sector, especially the teaching and learning process. In the midst of the covid-19 pandemic, teaching and learning activities are still being carried out even though they are not carried out face-to-face but online. One alternative to support this online teaching and learning process is to use WA groups. The purpose of this study was to determine the activities and learning outcomes carried out through WA groups. This study also aims to determine the improvement and learning outcomes of students through group work. This research uses quantitative methods by collecting data through in-depth surveys. The survey used in this research is a google form conducted online. The results of this study show that students' activities and learning outcomes increase when the group work learning process is conducted through WA Group. WA Group is also beneficial for students, because it saves the use of internet quota. The disadvantage of using WA Group in the process of increasing student activity is that students are easily influenced by other chats that can distract students from the teaching and learning process. The conclusion of this study explains that increasing student learning activities and outcomes through WA Group is very effective because students can use various features that can be accessed through WA Group.